The letter and spirit of biblical interpretation: from the early church to modern practice - Stanglin, Keith D. (Baker Academic, a division of Baker Publishing Group, 2018)
Introduction to the history of biblical interpretation -- Historical survey -- Earliest Christian exegesis -- Later patristic exegesis -- Medieval exegesis -- Early modern exegesis -- The rise of historical-critical exegesis -- Letter and spirit -- (Ir)reconcilable differences? -- A way forward